Query Expansion of Zero-Hit Subject Searches: Using a Thesaurus in Conjunction with NLP Techniques - Kapidakis, Sarantos; Mastora, Anna; Peponakis, Manolis (Lecture notes in computer science, 2012)
The focus of our study is zero-hit queries in keyword subject searches and the effort of increasing recall in these cases by reformulating and, then, expanding the initial queries using an external source of knowledge, namely a thesaurus. To this end, the objectives of this study are twofold. First, we perform the mapping of query terms to the thesaurus terms. Second, we use the matched terms to expand the user’s initial query by taking advantage of the thesaurus relations and implementing natural language processing (NLP) techniques. We report on the overall procedure and elaborate on key points and considerations of each step of the process.